The evolution of the governance and anti-corruption policies of the International Monetary Fund: 1990 - 2018 - Leousi, M (2020)
This thesis traces the evolution of anti-corruption policy in the International Monetary Fund (IMF or ‘the Fund’) since the 1990s. It also examines the specific operational consequences of corruption control efforts by the IMF. Three hypotheses are explored. First, at times of intense international security competition, the concern for corruption gets suppressed in favour of geopolitics. This means that the foreign policy priorities of the most powerful state(s) will modify the interests of the IMF, which in turn are shaped by fluctuating geostrategic competition. Second, as others have found, the Fund’s bureaucratic rules, i.e. its standard operating procedures, shape, categorise and classify how bureaucrats see the problem and create a ‘social world’ (Barnett and Finnemore, 2004, p. 18), and this defines its intervention. Put another way, the IMF bureaucracy is shaped by activities, understandings, identity and practices that define its culture and, subsequently, its response to corruption. Third, IMF policies are likely to be shaped by shifts in international norms, as per a ‘norms cascade’. Judged against these hypotheses, the thesis demonstrates how difficult it is to convert imprecise normative aspirations to control corruption into operational guidelines that can be applied in a consistent way by a major international organisation. The main findings regarding the first hypothesis are that geopolitical events of the magnitude of the Cold War and major financial crises – with variation in geopolitical intensity – compromise the IMF’s ability to act independently; US interests are robustly forced on the organisation; and the more geopolitically relevant a member state, the less anti-corruption-related pressure is exerted by the IMF. Regarding the second hypothesis, the thesis finds that first an international governmental organisation (IGO) – initiated by the member state or its management – comes to the realisation that it should get involved on governance issues. The reasons may vary according to the organisation and issue area. Second, the organisation rallies its resources, both its bureaucracy and its ideas, in order to support its involvement. Third, the organisation needs to make a case to its membership about why it is the best forum to deal with the issue, through the application of its policies. In terms of the third hypothesis, the thesis demonstrates that the emergence of non-governmental organisation (NGO) movements against corruption and the global attention they drew to corruption-related scandals, led to change in other international organisations, and created a backdrop against which the IMF was pushed to take action on anti-corruption. In sum, not only is the IMF constrained by geopolitical factors, it also faces complex and specific internal institutional opportunities and constraints, while also being influenced by external normative pressures. Taken together, the three sets of forces have at times limited the IMF’s intent and capacity to change, while at other times they have created an opportunity for change.